Hand Therapy Regimen for Functional Recovery Following Combined Face and Bilateral Hand Transplantation. (May 2023) - Boczar, Daniel; Seu, Monica; O'Connell, April; Gersh, Eugene; Chaya, Bachar F.; Berman, Zoe; Ruiz, Natalia; Welsh, Laura; Rodriguez, Eduardo D.
Intensive postoperative rehabilitation therapy is associated with positive functional recovery in hand transplants (HTs). Our goal is to share the hand therapy protocol developed for our patient who underwent a combined face and bilateral HT. The patient is a 23-year-old right-hand-dominant male with a history of third-degree burns to 80% of his body following a motor vehicle accident. A multidisciplinary evaluation established his candidacy for a combined face and bilateral HT, and surgery took place in August 2020. Our individualized hand therapy protocol consisted of 4 phases. The pre-surgery phase focused on planning the orthotics and patient/caregivers' education on the rehabilitation process. The intensive care unit (ICU)/acute care phase involved hand allograft protection and positioning via orthotic fabrication, safe limb handling, and edema/wound management. The inpatient rehabilitation phase aimed to prepare the patient for independent living via neuromuscular and sensory re-education, improvement of upper extremities strength/flexibility, training basic activities of daily living, and providing a home exercise program (HEP). Finally, the outpatient phase aimed to maximize our patient's range of motion and independency in performing his routine activities and HEP. The patient's post-transplant functional outcomes showed a significant improvement compared to the pre-operative baseline. We hope this report sheds light on a comprehensive hand therapy program in HT.